Strengthening Students' Character Through Local Wisdom: The Role of Tiba Meka Dance in Projek Penguatan Profil Pelajar Pancasila Activities - Arif Prasetyo Wibowo; Rose Fitria Lutfiana; Budiono; Nurbani Yusuf; Nurul Zuriah; Mifdal Zusron Alfaqi; Alice Sabrina Ismail; Gautam Kumar Jha (Jurnal Kewarganegaraan, 2026)
The implementation of character values through the Pancasila Student Profile is a complex task, facing various obstacles, particularly due to the rapid and often uncontrolled technological developments in the era of Society 5.0. This study employs a qualitative descriptive method, utilizing thematic analysis to identify key patterns in student character development, along with source triangulation to ensure the validity of findings. Based on this research, strengthening students' character through the integration of local wisdom in P5 activities at SMA Muhammadiyah Boleng, specifically through the Tiba Meka dance, has proven to be effective. Observations and interviews indicate a 30% increase in students’ cultural awareness, demonstrating that learning the Tiba Meka dance not only helps students recognize and preserve their cultural heritage but also cultivates discipline, responsibility, cooperation, and cultural pride. Furthermore, the active involvement of teachers and strong parental support significantly contribute to the success of this program. The findings highlight that the P5 initiative, through traditional dance, fosters character formation rooted in local identity and strengthens students' connection to their cultural heritage. This study suggests that integrating local wisdom into education, particularly through performing arts, is a practical and effective strategy for shaping students with strong personal and cultural values, offering valuable insights for the broader Indonesian educational system.